2022
DOI: 10.3390/antiox11112195
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Curcumin on 5/6Nx Hypertriglyceridemia: Association with the Improvement of Renal Mitochondrial β-Oxidation and Lipid Metabolism in Kidney and Liver

Abstract: Chronic kidney disease (CKD) prevalence is constantly increasing, and dyslipidemia in this disease is characteristic, favoring cardiovascular events. However, the mechanisms of CKD dyslipidemia are not fully understood. The use of curcumin (CUR) in CKD models such as 5/6 nephrectomy (5/6Nx) has shown multiple beneficial effects, so it has been proposed to correct dyslipidemia without side effects. This work aimed to characterize CUR’s potential therapeutic effect on dyslipidemia and alterations in lipid metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The effects on lipids were through increased expression of genes involved in lipolysis (hormone-sensitive lipase (HSL), adipose triglyceride lipase (ATGL) and lipoprotein lipase (LPL)), and in the signaling pathway of insulin (insulin receptor substrate 1 (IRS-1) and IRS-2). Also, allicin downregulated the expression of lipogenic genes (SREBP1, acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-CoA desaturase-1 (SCD-1), and activated receptor by peroxisome proliferator-γ (PPARγ)) ( Shi et al, 2019 ; Ashraf et al, 2005 ; Cannizzaro et al, 2017 ); this is particularly important as up-regulation of fatty acid synthesis is closely related with mitochondrial bioenergetics impairment in various models or renal damage, such as the induced by the unilateral ureteral obstruction, folic acid, and nephrectomy ( Ceja-Galicia et al, 2022 ; Martínez-Klimova et al, 2020 ; Kang et al, 2015 ). Furthermore, our results showed that allicin improved the electron flow in the mitochondria suggesting that restoration of mitochondrial bioenergetics could lead to protective effects in renal and plasma lipids.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on lipids were through increased expression of genes involved in lipolysis (hormone-sensitive lipase (HSL), adipose triglyceride lipase (ATGL) and lipoprotein lipase (LPL)), and in the signaling pathway of insulin (insulin receptor substrate 1 (IRS-1) and IRS-2). Also, allicin downregulated the expression of lipogenic genes (SREBP1, acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-CoA desaturase-1 (SCD-1), and activated receptor by peroxisome proliferator-γ (PPARγ)) ( Shi et al, 2019 ; Ashraf et al, 2005 ; Cannizzaro et al, 2017 ); this is particularly important as up-regulation of fatty acid synthesis is closely related with mitochondrial bioenergetics impairment in various models or renal damage, such as the induced by the unilateral ureteral obstruction, folic acid, and nephrectomy ( Ceja-Galicia et al, 2022 ; Martínez-Klimova et al, 2020 ; Kang et al, 2015 ). Furthermore, our results showed that allicin improved the electron flow in the mitochondria suggesting that restoration of mitochondrial bioenergetics could lead to protective effects in renal and plasma lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Since early CKD stages, nephron segments like proximal tubules increase their lipid levels [96,102] and the fatty acid uptake protein CD36 levels [102,104], associated with inflammatory pathways induction [105]. CKD lipotoxicity increases fatty acid levels in plasma and kidneys, especially palmitic acid [103,106,107]. Palmitic acid has been shown to inhibit the adenosine monophosphate (AMP)-activated protein kinase (AMPK) signaling, reducing mitochondrial function, and increasing mitochondrial ROS production to favor the NLRP3 inflammasome activation, caspase-1, IL-1β, and IL-18 production [107,108].…”
Section: Mitochondrial Dysfunction In Ckd Activates the Nlrp3-nf-κb P...mentioning
confidence: 99%
“…The higher fatty acid synthesis in CKD may also induce NLRP3 pathway activation by the fatty acid synthase (FASN) induction. This enzyme is upregulated in the remnant kidney of 5/6 nephrectomy rats [106], likely leading to upregulation of the expression of the inflammasome components: NLRP3, caspase-1, and pro-IL-1β [99]. Thus, renal mitochondria impairment could be an essential regulator of NLRP3 inflammasome activation during CKD.…”
Section: Mitochondrial Dysfunction In Ckd Activates the Nlrp3-nf-κb P...mentioning
confidence: 99%